2009
DOI: 10.1063/1.3085766
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface tension on nanotube nanofluids

Abstract: This letter presents heat transfer results that single-walled carbon nanotube ͑CNT͒ suspensions in a boiling environment can extend the saturated boiling regime and postpone catastrophic failure of the material even further than previously reported if the surface tension of the nanofluid is carefully controlled. The maximum enhancement in the critical heat flux is nearly four times for a surfactant to CNT concentration ratio of 1:5. The experimental results show that the material burnout is a strong function o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(42 citation statements)
references
References 13 publications
5
36
0
1
Order By: Relevance
“…Vafaei et al (2009) investigated the effects of size and concentration of nanoparticles on the effective gas-liquid surface tension of the aqueous solutions of the bismuth telluride nanoparticles. Kumar & Milanova (2009) found that the single-walled carbon nanotube suspensions in a boiling environment can extend the saturated boiling regime and postpone catastrophic failure of the materials even further than that previously reported if the surface tension of the nanofluids is carefully controlled. The surface tension of a liquid strongly depends on the presence of contaminants or dispersion agents such as surfactants.…”
Section: Surface Tension Of Nanofluidsmentioning
confidence: 76%
“…Vafaei et al (2009) investigated the effects of size and concentration of nanoparticles on the effective gas-liquid surface tension of the aqueous solutions of the bismuth telluride nanoparticles. Kumar & Milanova (2009) found that the single-walled carbon nanotube suspensions in a boiling environment can extend the saturated boiling regime and postpone catastrophic failure of the materials even further than that previously reported if the surface tension of the nanofluids is carefully controlled. The surface tension of a liquid strongly depends on the presence of contaminants or dispersion agents such as surfactants.…”
Section: Surface Tension Of Nanofluidsmentioning
confidence: 76%
“…(21). g nf ð4%SiO 2 ; 30nmÞ ¼ À0:1979T þ 61:97 with R 2 ¼ 0:9943 (21) Here T is in C and the Eq. (21) is valid in the range 30 C T 70 C.…”
Section: Concentration and Particle Size Effects On The Surface Tensionmentioning
confidence: 99%
“…Kumar and Milanova [21] measured the surface tension of single wall carbon nanotube (SWCNT) suspensions in deionized (DI) water with the surfactant NaBDS (Sodium salt of bis (1-dodecenyl succinamic acid)), using the bubble pressure method. Their results showed the surface tension of nanofluids were higher than those of the base fluid.…”
Section: Nanofluids Literature Surveymentioning
confidence: 99%
“…For nanofluids, however, surface tension depends on both temperature and nanoparticle concentration. Experimental studies for different nanofluids have reported that the presence of nanoparticles causes surface tension to be increased [30][31][32], to be unchanged [33,34] or to be decreased [4,35].…”
Section: Introductionmentioning
confidence: 98%